Los Títeres como estrategia didáctica y su influencia en el Aprendizaje Significativo de los niños de 4 y 5 años de edad en el Área de Lógico Matemática, de la I.E. Nº 303-Santa Rosa de Enace, del distrito de Rioja - 2006. - Maslucán Rojas, Lidia Guillermina (2007)
This investigation was born because we check many problems in the children's learning, in math logic, area. All this was born because the teacher don't want and don't have new didactic strategies that help to the students, being the best for them. By the way this investigation evaluate the new method that is based in the use of marionette, they help in the children's learning from 4 and 5 years in math logic area. We took as reference to the 1.E. number 303, ubicated in Santa Rosa from Enace in Rioja, because this institution presented many problems when we made the diagnostic. The pedagogic, psychology, history and cultural and the constructivism help us when we make the theoric course, it made the hypothesis, it get a conclusion, it was that, if then didactic strategies enter in the conduction of taaching-learning process we will get significative learning in the children, for that reason, the study show was a section of is children because this the l.E. 303 just has one section. In his operative part, the investigation was drive using the pre-experimental design of just one group, so, before we begin the experiment , we used a pretest, because we wanted to evaluated the previous knowledge of the children, this pretest was oppose with the post test before the didactic strategies application. For the statistic oppose of the hypothesis, we made "chi cuadrado" test, it result with 95% of trust for that reason we check that the learning of the students was better after of the marionette application in the teaching-learning process. By the way, in the range of calification for the children garden education, the children got the level that we wanted, it showed the acceptance of the hypothesis that we have in the investigation.